Ovarian tissue cryopreservation: a narrative review on cryopreservation and transplantation techniques, and the clinical outcomes - Zahra Karimizadeh; Zohreh Saltanatpour; Azadeh Tarafdari; Mahroo Rezaeinejad; Amir Ali Hamidieh (Therapeutic Advances in Reproductive Health)
Fertility preservation (FP) includes all the methods to preserve germ cells, reproductive tissues, or embryos for the future reproduction of patients at risk of infertility. Cryopreservation is an essential step of FP, storing the specimens in subzero temperatures to suppress cellular metabolism and restore cryopreserved specimens for future use. Although oocyte cryopreservation (OC) and embryo cryopreservation (EC) are two accepted methods of FP in women, ovarian tissue cryopreservation (OTC) is a novel method that is favorable in patients who are not appropriate candidates for OC and EC, and those who suffer from irritating menopause symptoms caused by estradiol deficiency. OTC has shown promising results in restoring fertility and the endocrine function of ovaries. Slow freezing and vitrification are two well-established methods for cryopreservation of biological specimens. Despite recent developments in the vitrification of ovarian tissue and comparable results to slow freezing, we lack a standard protocol for ovarian tissue vitrification, and slow freezing is still the preferred method in most centers. Under an acceptable medical condition and desirability, transplantation of cryopreserved tissue is performed either in orthotopic sites (orthotopic transplantation, OT) such as the original site of the ovaries and uterus, or heterotopic sites (heterotopic transplantation, HT) like abdominal wall, forearm, and peritoneal lining. Although both sites of transplantation are associated with endocrine function recovery, OT better restores fertility. This review will focus on OTC and its types, ovarian tissue transplantation, and efficacy in clinical practice.